PENGARUH KUALITAS PELAYANAN PAJAK, PENERAPAN E-FILLING DAN E-BILLING TERHADAP KEPUASAN WAJIB PAJAK - Wahdini; Rusdi (Jurnal Nusa Akuntansi, 2024)
This research aims to scientifically test and prove the influence of Tax Service Quality, Implementation of e-filling and E-billing on Individual Taxpayer Satisfaction, a case study of taxpayers registered at KPP Pratama Pondok Aren. This type of research uses quantitative research, in-depth analysis in the form of numbers. The population in this research is individual taxpayers at KPP Pratama Pondok Aren. The sample in the study was determined based on the simple random sampling method. The number of respondents sampled in this study was 100 respondents. Data was collected using a questionnaire and analyzed using multiple regression using the SPSS version 27 program. The research results show that the influence of Tax Service Quality, Implementation of e-filling and Implementation of E-billing has a significant and significant impact on Taxpayer Satisfaction. This shows the importance of these independent factors in increasing taxpayer satisfaction in the case study of taxpayers registered at KPP Pratama Pondok Aren